Organophosphate Induced Delayed Neuropathy (OPIDN) - Basak, PM; Begum, MM; Islam, MJ; Khan, FA; Das, HS; Jahan, KI (TAJ: Journal of Teachers Association, 2018)
A 13 years old boy who consumed organophosphorous compound later on developed delayed neuropathy is described. TAJ 2014; 27(1): 62-63